2014
DOI: 10.3354/esr00576
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial analysis of habitat use by silver hake Merluccius bilinearis in the Gulf of Maine

Abstract: Three theories of habitat use proposed for marine fishes, the constant density model (CDM), the proportional density model (PDM), and the basin model (BM), make contrasting predictions of how the range, local density, and fitness change as population size changes. We tested model predictions using a survey of silver hake Merluccius bilinearis conducted by the National Marine Fisheries Service every spring and fall. Data on fish length, sex, weight, and reproductive status are collected. Despite a 50% populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…The geostatistical aggregation curves suggest that during the study period, G. argenteus exhibited a proportional density population structure in which local abundance changes in proportion to changes in total species abundance. This is consistent with the proportional density dynamic model (D2) (Petitgas 1998) which is driven by a site-dependent mechanism (Petitgas 1998, Pereira et al 2014, namely, the physical habitat preferences of the species during the period 1998−2019 were not modified by changes in its annual abundance. This spatial pattern has been previously observed in gadiforms in the eastern (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The geostatistical aggregation curves suggest that during the study period, G. argenteus exhibited a proportional density population structure in which local abundance changes in proportion to changes in total species abundance. This is consistent with the proportional density dynamic model (D2) (Petitgas 1998) which is driven by a site-dependent mechanism (Petitgas 1998, Pereira et al 2014, namely, the physical habitat preferences of the species during the period 1998−2019 were not modified by changes in its annual abundance. This spatial pattern has been previously observed in gadiforms in the eastern (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…This spatial pattern has been previously observed in gadiforms in the eastern (e.g. Houghton 1987, Petitgas 1998, González-Irusta & Wright 2016a,b, 2017 and western North Atlantic (Tamdrari et al 2010, Pereira et al 2014.…”
Section: Discussionsupporting
confidence: 82%
“…In addition to oceanographic drivers influencing the spatial distribution of Silver Hake, Reed et al (2019) found that the condition of Silver Hake on the Scotian Shelf was largely determined by zooplankton phenology and community composition and was largely unrelated to density-dependent effects. A geospatial analysis of Silver Hake in the GOM indicated that condition varied over small spatial scales and that the population conformed to the proportional density model, in which local population density is a static proportion of the fixed occupied range (Pereira et al 2014). In contrast to the other moderate-quality species, longfin inshore squid had lower predicted EDs offshore and south (GB and Middle Atlantic Bight) than in the north (GOM) during spring.…”
Section: Moderate-quality Preymentioning
confidence: 89%
“…A geospatial analysis of Silver Hake in the GOM indicated that condition varied over small spatial scales and that the population conformed to the proportional density model, in which local population density is a static proportion of the fixed occupied range (Pereira et al. 2014). In contrast to the other moderate‐quality species, longfin inshore squid had lower predicted EDs offshore and south (GB and Middle Atlantic Bight) than in the north (GOM) during spring.…”
Section: Discussionmentioning
confidence: 99%
“…The 4 case study articles presented in this section review the application and advancement of habitatbased models for pelagic species. Pereira et al (2014, this Theme Section) tested 3 predictions of silver hake Merluccius bilinearis distributions and found that this species demonstrated site-dependent patterns of habitat use in the Gulf of Maine, which may be important for its persistence.…”
Section: Case Studies: California Current and Beyondmentioning
confidence: 99%